METHODS OF ASSESSING CIRCADIAN EFFICIENCY OF DIFFERENT TYPES OF SOURCES - and (Municipal economy of cities. Series: «Economy science», 2013)
The determining method of different types light sources circadian efficiency by the number of photon lamps radiation energy in the wavelength range 380-580 nm has been proposed.